2021
DOI: 10.1021/acs.energyfuels.1c02576
|View full text |Cite
|
Sign up to set email alerts
|

Using New Synthesis Zirconia-Based Nanocomposites for Improving Water Alternative Associated Gas Tests Considering Interfacial Tension and Contact Angle Measurements

Abstract: The use of nanoparticles is a known solution for challenges related to enhanced oil recovery (EOR) methods, and nanoparticles have good potential for changing effective mechanisms, such as wettability alteration and interfacial tension (IFT) reduction. On the basis of our last research, it was observed that using associated gas in a water alternative gas (WAG) method has a high recovery potential in comparison to other gases, such as CO 2 and N 2 , in carbonate reservoirs. In this study, zeolite−zirconia−ceriu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 75 publications
0
5
0
Order By: Relevance
“…They are commonly used in various applications, including industrial catalysts in the petrochemical industry for acid-catalyzed reactions, molecular sieves, and ion exchange systems [69], [70]. Zeolites' porous properties and chemical composition are highly utilized in diverse industrial applications, including petroleum refining, petrochemicals, and natural gas treatment [71], [72]. Using zeolites for conformance control is attractive because they are highly selective and have low permeability, making them effective at reducing the flow of unwanted fluids.…”
Section: Bentonite Colloidsmentioning
confidence: 99%
“…They are commonly used in various applications, including industrial catalysts in the petrochemical industry for acid-catalyzed reactions, molecular sieves, and ion exchange systems [69], [70]. Zeolites' porous properties and chemical composition are highly utilized in diverse industrial applications, including petroleum refining, petrochemicals, and natural gas treatment [71], [72]. Using zeolites for conformance control is attractive because they are highly selective and have low permeability, making them effective at reducing the flow of unwanted fluids.…”
Section: Bentonite Colloidsmentioning
confidence: 99%
“…In some research, chemical-enhanced oil recovery (CEOR) methods have been used to solve this problem by providing mechanisms such as interfacial tension (IFT) reduction and wettability alteration (WA). Nanotechnology in the oil industry has significant capacity and potential in oil reservoirs to meet growing energy needs. Nanoparticles in enhanced oil recovery (EOR) processes in oil reservoirs are an emerging technique, and their impact on oil reservoirs is increasing rapidly. The use of nanoparticles can be promising in many fields. Several nanoparticles (such as Al 2 O 3 and SiO 2 ) have been studied in EOR, and some nanoparticles have shown acceptable potential in EOR processes. Recently, ZnO nanoparticles have been able to help oil production by various mechanisms to reduce oil viscosity and change wettability. However, the reported results regarding using ZnO in the direction of IFT are still controversial. In this regard, some studies claim that ZnO nanoparticles increase the IFT, and, on the other hand, some reports claim that ZnO reduces IFT .…”
Section: Introductionmentioning
confidence: 99%
“…Nanoparticles in enhanced oil recovery (EOR) processes in oil reservoirs are an emerging technique, and their impact on oil reservoirs is increasing rapidly. 12 19 The use of nanoparticles can be promising in many fields. 20 23 Several nanoparticles (such as Al 2 O 3 and SiO 2 ) have been studied in EOR, and some nanoparticles have shown acceptable potential in EOR processes.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that ZrO 2 nano-particles have a great application in EOR. Based on the results, nano-assisted water-alternative associated gas test in the presence of nano-composites [zeolite–zirconia­(ZrO 2 )–cerium oxide­(CeO 2 )] increased tertiary oil recovery increased up to 29% . In other work, Alomair et al used ZrO 2 , TiO 2 , Fe 2 O 3 , and ZnO nano-particles for EOR.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the results, nano-assisted water-alternative associated gas test in the presence of nano-composites [zeolite–zirconia(ZrO 2 )–cerium oxide(CeO 2 )] increased tertiary oil recovery increased up to 29%. 24 In other work, Alomair et al 25 used ZrO 2 , TiO 2 , Fe 2 O 3 , and ZnO nano-particles for EOR. It was observed that oil recovery (in the presence of ZrO 2 nano-particles) was improved by up to 68%.…”
Section: Introductionmentioning
confidence: 99%